An MPPT-based 31-Level ADC Controlled Micro-Inverter - Shah, M. J.; Pandya, K. S.; Chauhan, P. (Engineering, Technology & Applied Science Research, 2022)
This paper presents a 31-level micro-inverter with an innovative control scheme. The presented micro-inverter makes use of a single PV panel connected to an MPPT converter. Four half-bridge legs are connected in series to produce 31 levels at the inverter’s output. At the output side of the micro-inverter, a single full-bridge power circuit is used to generate positive and negative half-cycles. A high-frequency transformer and a push-pull converter are used to generate the required isolated DC sources. The output of an Analog to Digital Converter (ADC) is used as a gate pulse for the half-bridge circuit power switching devices. PSIM software was used to simulate the proposed micro-inverter, and the results are discussed. Hardware prototypes were also created and the results are displayed.